Organic-inorganic hybrid flame-retardant adhesive and preparation method thereof

The organic-inorganic hybrid flame retardant adhesive prepared through covalent crosslinking reaction solves the flammability problem of wood plywood, achieves high strength, excellent flame retardant performance and water resistance, and meets the safety needs of the construction and furniture industries.

CN119505742APending Publication Date: 2025-02-25SOUTHWEST FORESTRY UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411677823.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-22
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The prior art lacks a safe and environmentally friendly organic-inorganic hybrid flame retardant adhesive and its preparation method, and it is difficult to effectively solve the flammability problem of wood plywood while maintaining good mechanical properties.

Method used

An organic-inorganic hybrid flame retardant adhesive was prepared by covalently crosslinking of oxidized chitosan (OCTS), hyperbranched polymer (HPA), and surface-modified vermiculite nanosheets (VMT NSs-NH2).

Benefits of technology

It realizes the super glue strength, excellent flame retardant properties and good water resistance of plywood, and has a simple process and low cost, meeting the safety needs of the construction and furniture industries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119505742A_ABST
    Figure CN119505742A_ABST
Patent Text Reader

Abstract

The invention discloses an organic-inorganic hybrid flame-retardant adhesive and a preparation method thereof, the adhesive is composed of oxidized chitosan (OCTS), a hyperbranched polymer (HPA) and vermiculite nanosheets (VMT NSs-NH2) of which the surfaces are modified with amino groups, and the adhesive is formed by covalent crosslinking through Schiff base reaction. The adhesive has super-strong bonding strength, water resistance and good flame retardant property. The interfacial compatibility between the VMT NSs-NH2 nano material and the adhesive is enhanced through the intermediary effect of the HPA, and the uniform dispersion of the adhesive is promoted. Through hot-pressing curing, the organic-inorganic hybrid flame-retardant adhesive can be used for gluing wood, and has excellent gluing performance and flame-retardant performance. This combination results in a wood bond strength of 1.7 MPa, a limit oxygen index of 36.7%, and excellent cone calorimetry results. The raw materials used in the invention are green, nontoxic, free of formaldehyde addition, safe and environment-friendly, and the adhesive has super-strong bonding strength, water resistance and good flame retardant property.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of material science and engineering application technology, and in particular to an organic-inorganic hybrid flame retardant adhesive and a flame retardant plywood and a preparation method thereof. Background Art

[0002] Wood adhesives play an increasingly important role in wood processing, furniture manufacturing and construction. The main wood adhesives on the market include urea formaldehyde (UF), phenol formaldehyde (PF) and melamine formaldehyde (MF) adhesives. Although these adhesives have good performance, they have some problems, such as non-renewable raw materials and the release of harmful substances such as formaldehyde. Therefore, people have begun to turn to the development of bio-based adhesives.

[0003] Bio-based adhesives use renewable biomass resources such as cellulose, tannin, lignin, soy protein and chitosan. Among them, chitosan is regarded as an alternative to traditional formaldehyde-based adhesives due to its biocompatibility, degradability and film-forming ability. However, the high brittleness and low water resistance of chitosan limit its application. To solve these problems, researchers have adopted a variety of methods, such as adding plasticizers, cross-linking modification and constructing branched structures. The use of dendrimers as cross-linkers can improve the bonding properties and water resistance of chitosan-based adhesives, but may increase brittleness. Hyperbranched polymers, especially hyperbranched polysiloxanes, can effectively enhance the toughness of thermosetting resins due to their unique structure and properties.

[0004] In the construction and furniture sectors, the flammability of plywood increases the risk of fire. The traditional flame retardant strategy is to add granular flame retardants, but this may affect the mechanical properties of plywood. Vermiculite, a natural flame retardant mineral, is becoming increasingly popular in polymer composites due to its fire retardant properties and lightweight characteristics. By mimicking the structure of mother-of-pearl and introducing chemically modified vermiculite to improve the cross-linked network, the researchers not only improved the flame retardancy of the adhesive, but also solved the problem of easy leaching of inorganic materials.

[0005] Currently, there is a lack of a safe and environmentally friendly organic-inorganic hybrid flame retardant adhesive and a preparation method thereof. Summary of the invention

[0006] The object of the present invention is to provide a safe and environmentally friendly organic-inorganic hybrid flame retardant adhesive and a preparation method thereof.

[0007] In order to solve the problems of the prior art, the present invention provides the following technical solutions:

[0008] In a first aspect, the present application provides a method for preparing an organic-inorganic hybrid flame retardant adhesive.

[0009] In a second aspect, the present application provides an organic-inorganic hybrid flame retardant adhesive.

[0010] In a third aspect, the present application provides an organic-inorganic hybrid flame retardant adhesive and a flame retardant plywood for use in the preparation of a flame retardant adhesive.

[0011] The first aspect of the present application provides a method for preparing an organic-inorganic hybrid flame retardant adhesive, comprising the following steps: the organic-inorganic hybrid flame retardant adhesive is composed of oxidized chitosan OCTS, a hyperbranched polymer HPA and vermiculite nanosheets VMT NSs-NH2 with surface modified amino groups, and oxidized chitosan, hyperbranched polymer HPA and surface modified vermiculite nanosheets are added respectively, and a covalent cross-linking reaction is carried out through a Schiff base reaction to obtain an organic-inorganic hybrid flame retardant adhesive.

[0012] Further, (1) oxidized chitosan OCTS, hyperbranched polymer HPA and vermiculite nanosheets VMTNSs-NH 2 ;

[0013] (2) mixing oxidized chitosan OCTS and hyperbranched polymer HPA at a molar ratio of 1:1;

[0014] (3) Adding vermiculite nanosheets VMT NSs-NH 2 The mass fraction is 1-10%;

[0015] (4) The added components are covalently cross-linked through a Schiff base reaction to prepare an organic-inorganic hybrid flame retardant adhesive.

[0016] Further, in step (1), preparation of hyperbranched polymer HPA: 0.4 mol of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 mol of triethanolamine TEA and 0.1% of p-toluenesulfonic acid (p-TSA) are placed in a 250 ml three-necked flask with a distillation apparatus, heated to 120° C. under a nitrogen atmosphere, and maintained at this temperature until the by-product ethanol is distilled off. Then the temperature of the system is maintained at 180° C. until no distillation by-product is generated.

[0017] Further, in step (1), the preparation of vermiculite nanosheets VMTNSs-NH2: 5.0 g of VMT powder was placed in 500 ml of 36% saturated sodium chloride solution, concentrated and refluxed at 120°C for 2 hours, and after cooling to room temperature, the sample was filtered and rinsed with deionized water and ethanol to remove excess salt; then, the sodium-exchanged VMT was dispersed in 300 ml of 2M solution, refluxed at 120°C for 2 hours and cooled to room temperature, the sample was filtered and rinsed with deionized water, and the collected sample was subjected to tip ultrasound at low temperature below 10°C for 60 minutes, and then the dispersion containing single-layer or multi-layer VMT nanosheets was further separated, and the sample was centrifuged at 3000 rpm for 30 minutes to remove multi-layer / blocky residues. 1 g of VMT NSs was initially dispersed in 50 ml of toluene. Subsequently, a stable suspension was formed by continuous mechanical stirring for 6 hours to ensure that the VMTNSs were evenly distributed in the solvent. This suspension was then transferred to an ultrasonic cleaning tank, during which 6.2 ml of 3-aminopropyltriethoxysilane APTES was gradually added dropwise to promote the binding of APTES molecules to the clay surface. The ultrasonic process lasted for thirty minutes, and after the ultrasonic process was completed, the dispersion was filtered and rinsed with ethanol several times to completely remove the unreacted APTES; finally, the washed clay sample was dried in a vacuum oven at 120 ° C for 12 hours to ensure the complete removal of all solvents and moisture, and the grafted clay was designated as VMT NSs-NH2.

[0018] Furthermore, in step (1), oxidized chitosan OCTS is prepared by dissolving 1.0 g of chitosan in 100 ml of acetic acid solution at a concentration of 1% and mechanically stirring at room temperature for 2 hours. Different amounts of sodium periodic acid are dissolved in deionized water, with a weight ratio of oxidant to chitosan of 1.0, and added to the chitosan solution under magnetic stirring; the mixture is heated to 40°C and stirred in the dark for 3 hours; after cooling to room temperature, an appropriate amount of ethanol is added. The white precipitate is separated by filtration and washed three times with deionized water; finally, OCTS is dried at room temperature for 24 hours.

[0019] The method for preparing the organic-inorganic hybrid flame retardant adhesive of the invention prepares the organic-inorganic hybrid flame retardant adhesive.

[0020] The invention discloses a wood bonding method using an organic-inorganic hybrid flame retardant adhesive, which is characterized by comprising the following steps: applying the adhesive to the wood surface, hot pressing at 100° C.-180° C. for 240-600 seconds, and then placing at room temperature for 24 hours to eliminate internal stress.

[0021] The invention discloses a method for preparing a flame retardant coating, comprising the following steps: dissolving disodium octaborate tetrahydrate hydrate in water to form a transparent solution, and then applying the solution to the surface of a plywood bonded with a flame retardant adhesive.

[0022] The method for preparing a flame-retardant plywood of the present invention comprises the following steps: using a bonding method.

[0023] Beneficial effects: The raw materials used in the present invention are green and non-toxic, no aldehyde is added, safe and environmentally friendly, and the adhesive has super strong bonding strength, water resistance and good flame retardant properties.

[0024] Compared with the prior art, the present invention has the following advantages: (1) Super strong bonding strength of the present invention: VMT NSs-NH 2 Combined with OCTS, a microscopic phase-separated structure similar to the exoskeleton of marine arthropods was formed, and this combination produced a wood bond strength of 1.7MPa.

[0025] (2) Excellent flame retardant properties: The plywood prepared by the organic-inorganic hybrid flame retardant adhesive of the present invention has a limiting oxygen index of 36.7% and excellent cone calorimetry test results, showing good flame retardant properties. Water resistance: After the adhesive of the present invention is soaked in 63°C hot water for 3 hours, the bonding strength of the plywood can still reach 1.4MPa. Even after soaking in boiling water for 3 hours, the bonding strength only slightly decreases to 1.2MPa, showing excellent water resistance.

[0026] (3) Enhanced interfacial compatibility: The interfacial compatibility of VMTNSs-NH 2 The interfacial compatibility between the nanomaterial and the adhesive promotes uniform dispersion of the adhesive. Simple preparation method: The preparation method of the organic-inorganic hybrid flame retardant adhesive of the present invention is simple and low in cost.

[0027] (4) Improve the safety of the wood industry: Through innovative flame retardant technology, the safety of plywood has been improved to meet the needs of the construction and furniture industries. Reduce environmental and health impacts: By improving the formula and process, the performance of adhesives has been improved and the impact on the environment and human health has been reduced.

[0028] (5) Broad application prospects: The biomimetic flame retardant adhesive of the present invention has broad application prospects in the wood industry and can provide an environmentally friendly and efficient bonding solution. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] The drawings constituting a part of the present application are used to provide a further understanding of the present application. The illustrative embodiments and descriptions of the present application are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0030] Figure 1 HPA / OCTS / VMTNSs-NH of the adhesive of the present invention 2 Diagram of the reaction process and mechanism of nanocomposites.

[0031] Figure 2 It is a schematic diagram of the cross-linking network of the adhesive reaction of the present invention.

[0032] Figure 3 The chemical characterization data diagram of the intermediate material and the prepared adhesive in the steps of the present invention. DETAILED DESCRIPTION

[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0034] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.

[0035] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.

[0036] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.

[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.

[0038] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.

[0039] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of indicated technical features. For example, without departing from the scope of the embodiments of the present application, the first XX may also be referred to as the second XX, and similarly, the second XX may also be referred to as the first XX. Thus, features defined as "first" and "second" may explicitly or implicitly include one or more of the features.

[0040] The first aspect of the embodiment of the present application provides a method for preparing an organic-inorganic hybrid flame retardant adhesive, comprising the following steps: preparing the organic-inorganic hybrid flame retardant adhesive from oxidized chitosan OCTS, a hyperbranched polymer HPA and vermiculite nanosheets VMTNSs-NH 2 The composition of the adhesive was prepared by adding oxidized chitosan, hyperbranched polymer HPA, and surface-modified vermiculite nanosheets, respectively, and covalently cross-linking through Schiff base reaction to obtain an organic-inorganic hybrid flame retardant adhesive. Oxidized chitosan (OCTS): It is a natural polysaccharide with good biocompatibility and biodegradability. It can be obtained from chitosan by chemical or physical methods, and has enhanced hydrophilicity and reactivity. Hyperbranched polymer (HPA): It has a highly branched structure and can provide multiple reaction sites to increase the cross-linking density and mechanical strength of the adhesive. Surface-modified vermiculite nanosheets (VMT NSs-NH 2 ): Vermiculite is a layered silicate mineral. After surface modification, its compatibility with organic polymers can be improved and the flame retardant properties of adhesives can be enhanced.

[0041] In some embodiments, (1) oxidized chitosan OCTS, hyperbranched polymer HPA and vermiculite nanosheets VMT NSs-NH are prepared respectively. 2 ;

[0042] (2) mixing oxidized chitosan OCTS and hyperbranched polymer HPA at a molar ratio of 1:1;

[0043] (3) Adding vermiculite nanosheets VMT NSs-NH 2 The mass fraction is 1-10%;

[0044] (4) The added components are covalently cross-linked through a Schiff base reaction to prepare an organic-inorganic hybrid flame retardant adhesive.

[0045] In some embodiments, in step (1), the preparation of hyperbranched polymer HPA is to take 0.4 mol of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 mol of triethanolamine TEA and 0.1% of p-toluenesulfonic acid (p-TSA), put them into a 250 ml three-necked flask with a distillation apparatus, heat to 120° C. under a nitrogen atmosphere, and maintain this temperature until the by-product ethanol is distilled off. Then the temperature of the system is maintained at 180° C. until no distillation by-product is produced.

[0046] In some embodiments, in step (1), the vermiculite nanosheets VMTNSs-NH 2 For the preparation, 5.0 g of VMT powder was placed in 500 mL of 36% saturated sodium chloride solution, concentrated and refluxed at 120 °C for 2 h. After cooling to room temperature, the sample was filtered and rinsed with deionized water and ethanol to remove excess salt. Then, the sodium-exchanged VMT was dispersed in 300 mL of (2M) solution. After refluxing at 120 °C for 2 h and cooling to room temperature, the sample was filtered and rinsed with deionized water. The collected samples were sonicated using a tip at low temperature below 10 °C for 60 min. The dispersion containing single or multilayer VMT nanosheets was then used for further separation. The sample was centrifuged at 3000 rpm for 30 min to remove multilayer / blocky residues. 1 g of VMT NSs was initially dispersed in 50 mL of toluene. Subsequently, a stable suspension was formed by continuous mechanical stirring for 6 h to ensure uniform distribution of VMT NSs in the solvent. This suspension was then transferred to an ultrasonic cleaning tank. During the ultrasonication process, 6.2 ml of 3-aminopropyltriethoxysilane (APTES) was gradually added dropwise to promote the binding of APTES molecules to the clay surface. The ultrasonication process lasted for thirty minutes. After the ultrasonication was completed, the dispersion was filtered and rinsed with ethanol several times to completely remove the unreacted APTES. Finally, the washed clay sample was dried in a vacuum oven at 120 °C for 12 hours to ensure the complete removal of all solvents and moisture. The resulting grafted clay was designated as VMT NSs-NH 2 .

[0047] In some embodiments, in step (1), the preparation of oxidized chitosan (OCTS) is to dissolve 1.0 g of chitosan in a 1% acetic acid solution (100 ml) and mechanically stir at room temperature for 2 hours. Different amounts of sodium periodic acid are dissolved in deionized water (weight ratio of oxidant / chitosan = 1.0) and added to the chitosan solution under magnetic stirring. The mixture is heated to 40°C and stirred for 3 hours in the dark. After cooling to room temperature, an appropriate amount of ethanol is added. The white precipitate is separated by filtration and washed three times with deionized water. Finally, OCTS is dried at room temperature for 24 hours.

[0048] (4) mixing oxidized chitosan OCTS with hyperbranched polymer HPA in a molar ratio of 1:1. This ratio can adjust the viscosity and mechanical properties of the adhesive to meet different application requirements;

[0049] (5) Adding vermiculite nanosheets VMT NSs-NH 2 The mass fraction of is 1-10%, which can ensure that the adhesive has good flame retardant properties without significantly affecting its bonding performance;

[0050] (6) Covalent crosslinking via Schiff base reaction; Schiff base reaction is an effective covalent crosslinking method that can be used in oxidized chitosan OCTS, hyperbranched polymer HPA, and vermiculite nanosheets VMT NSs-NH 2 Stable chemical bonds are formed between the two, thus enhancing the stability and durability of the adhesive and producing an organic-inorganic hybrid flame retardant adhesive.

[0051] A second aspect of an embodiment of the present application provides a method for preparing an organic-inorganic hybrid flame retardant adhesive to prepare the organic-inorganic hybrid flame retardant adhesive.

[0052] The third aspect of the embodiment of the present application provides a method for bonding wood using an organic-inorganic hybrid flame retardant adhesive, comprising the following steps: applying the adhesive to the wood surface, hot pressing at 100°C-180°C for 240-600 seconds, and then leaving it at room temperature for 24 hours to eliminate internal stress. Post-treatment: This step helps to improve the long-term stability of the adhesive and reduce cracks that may occur during the wood bonding process.

[0053] A fourth aspect of the embodiments of the present application provides a method for preparing a flame-retardant plywood, a bonding method used therein, and a flame-retardant coating.

[0054] A fifth aspect of an embodiment of the present application provides a method for preparing a flame retardant coating, comprising the following steps: dissolving disodium octaborate tetrahydrate hydrate in water to form a transparent solution, and then applying the solution to the surface of a plywood.

[0055] Example 1

[0056] A method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention comprises the following steps:

[0057] (1) Preparation of HPA 0.4 mol of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 mol of triethanolamine TEA and 0.1% of p-toluenesulfonic acid (p-TSA) were placed in a 250 ml three-necked flask equipped with a distillation apparatus, heated to 120° C. under a nitrogen atmosphere, and maintained at this temperature until the by-product ethanol was distilled off. The temperature of the system was then maintained at 180° C. until no distillation by-product was produced.

[0058] Vermiculite Nanosheets VMT NSs-NH 2 For the preparation, 5.0 g of VMT powder was placed in 500 mL of 36% saturated sodium chloride solution, concentrated and refluxed at 120 °C for 2 h. After cooling to room temperature, the sample was filtered and rinsed with deionized water and ethanol to remove excess salt. Then, the sodium-exchanged VMT was dispersed in 300 mL of (2M) solution. After refluxing at 120 °C for 2 h and cooling to room temperature, the sample was filtered and rinsed with deionized water. The collected samples were sonicated using a tip at low temperature below 10 °C for 60 min. The dispersion containing single or multilayer VMT nanosheets was then used for further separation. The sample was centrifuged at 3000 rpm for 30 min to remove multilayer / blocky residues. 1 g of VMT NSs was initially dispersed in 50 mL of toluene. Subsequently, a stable suspension was formed by continuous mechanical stirring for 6 h to ensure uniform distribution of VMT NSs in the solvent. This suspension was then transferred to an ultrasonic cleaning tank. During the ultrasonication process, 6.2 ml of 3-aminopropyltriethoxysilane (APTES) was gradually added dropwise to promote the binding of APTES molecules to the clay surface. The ultrasonication process lasted for thirty minutes. After the ultrasonication was completed, the dispersion was filtered and rinsed with ethanol several times to completely remove the unreacted APTES. Finally, the washed clay sample was dried in a vacuum oven at 120 °C for 12 hours to ensure the complete removal of all solvents and moisture. The resulting grafted clay was designated as VMT NSs-NH 2 .

[0059] Preparation of oxidized chitosan (OCTS) 1.0 g of chitosan was dissolved in 1% acetic acid solution (100 ml) and mechanically stirred at room temperature for 2 h. Different amounts of sodium periodic acid were dissolved in deionized water (weight ratio of oxidant / chitosan = 1.0) and added to the chitosan solution under magnetic stirring. The mixture was heated to 40°C and stirred for 3 h in the dark. After cooling to room temperature, an appropriate amount of ethanol was added. The white precipitate was separated by filtration and washed three times with deionized water. Finally, OCTS was dried at room temperature for 24 h.

[0060] (2) dissolving 2 g of OCTA in 2 g of water to obtain an OCTA solution;

[0061] (3) Add 0.4 g of VMTNSS-NH to 4 g of OCTS aqueous solution 2 and 2 g of HPA, stirred at room temperature for 30 minutes, and then gradually added hydrochloric acid until the pH value of the solution reached 6, thereby obtaining an organic-inorganic hybrid flame retardant adhesive.

[0062] A method for using an organic-inorganic hybrid flame retardant adhesive of the present invention comprises the following steps:

[0063] The prepared organic-inorganic hybrid flame retardant adhesive is coated on a plywood and hot-pressed at 160° C. for 360 seconds. The prepared plywood is left for 24 hours to eliminate internal stress.

[0064] Disodium octaborate tetrahydrate hydrate was dissolved in water to form a transparent solution, which was then applied to the surface of the plywood.

[0065] Example 2

[0066] The only difference between Example 2 and Example 1 is that the preparation method of an organic-inorganic hybrid flame retardant adhesive of the present invention comprises the following steps: in step (1), the hot pressing temperature is 100°C, and the remaining process steps and parameters are the same as those in Example 1.

[0067] Example 3

[0068] The only difference between Example 3 and Example 1 is that the preparation method of an organic-inorganic hybrid flame retardant adhesive of the present invention comprises the following steps: the hot pressing temperature in step (1) is 120°C, and the remaining process steps and parameters are the same as those in Example 1.

[0069] Example 4

[0070] The only difference between Example 4 and Example 1 is that in the method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention, in step (1), the hot pressing temperature is 140°C, and the remaining process steps and parameters are the same as those in Example 1.

[0071] Example 5

[0072] The only difference between Example 5 and Example 1 is that in the method of the present invention for preparing an organic-inorganic hybrid flame retardant adhesive, in step (1), the hot pressing temperature is 180° C., and the remaining process steps and parameters are the same as those in Example 1.

[0073] Example 6

[0074] The only difference between Example 6 and Example 1 is that in the method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention, in step (1), the hot pressing time is 240s, and the remaining process steps and parameters are the same as those in Example 1.

[0075] Example 7

[0076] The only difference between Example 7 and Example 1 is that in the method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention, in step (1), the hot pressing time is 480s, and the remaining process steps and parameters are the same as those in Example 1.

[0077] Example 8

[0078] The only difference between Example 8 and Example 1 is that in the method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention, in step (1), the hot pressing time is 600s, and the remaining process steps and parameters are the same as those in Example 1.

[0079] Comparative Example 1

[0080] The difference between Comparative Example 1 and Example 1 is that in the method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention, in step (1), HPA is not added, and the remaining process steps and parameters are the same as those in Example 1.

[0081] Comparative Example 2

[0082] The difference between Comparative Example 2 and Example 1 is that: in the method for preparing an organic-inorganic hybrid flame retardant adhesive of the present invention, in step (1), no VMT NSs-NH 2 The remaining process steps and parameters are the same as those in Example 1.

[0083] The physical and mechanical properties of the above materials were tested using a universal mechanical testing machine, and the bonding strength of the plywood was tested according to GB / T17657-2022 standard. The results of the bonding strength table are shown in Table 1.

[0084] Table 1

[0085] Plywood test piece Bonding strength (MPa) Example 1 1.7 Example 2 0.8 Example 3 1.0 Example 4 1.2 Example 5 1.2 Example 6 1.3 Example 7 1.4 Example 8 1.7 Comparative Example 1 0.4 Comparative Example 2 1.4

[0086] Comparative Example 21.4 From the bonding strength data in Table 1, it can be seen that OCTS / HPA / VMT NSs-NH 2 The bonding performance of the prepared plywood is much higher than that of OCTS / VMT NSs-NH 2 This also shows that the bonding performance of the prepared plywood can be further improved after adding HPA solution.

[0087] The flame retardant properties of plywood were tested according to the ISO 4589-2 limiting oxygen index test standard. The limiting oxygen index results are shown in Table 2.

[0088] Table 2

[0089]

[0090] Figure 1 The reaction process and mechanism diagram of the HPA / OCTS / VMT NSs-NH2 nanocomposite material of the adhesive of the present invention;

[0091] Figure 2 The cross-linked network principle diagram of the adhesive reaction of the present invention. Through careful X-ray photoelectron spectroscopy (XPS) analysis, we have confirmed the chemical composition and elemental state of the product surface, such as Figure 2 During the detailed examination of the chemical composition and elemental state of the product surface, we observed OCTS (compound) and OCTS / VMT NSs-NH 2 Comparative analysis of C1s peaks between composites. The decrease of C=O (285.9 eV) is especially accompanied by the appearance of C=N (286.5 eV) peak, indicating that the aldehyde group (-CHO) of OCTS is closely related to the VMT NSs-NH 2 The amino group (-NH 2 ) between the two groups. This finding is further supported by the comparison of the O1s spectra, where the reduction of the C=O (531.8 eV) peak confirms the chemical reaction process. Continuing the comparative analysis, the C1s signal of the HPA / OCTS system also shows a reduction in the C=O (285.9 eV) peak and the appearance of the C=N peak, with a corresponding reduction in the C=O (531.8 eV) peak in the O1s spectrum. Most importantly, in the HPA / OCTS / VMTNSs-NH 2 The observed changes in the C1s and O1s spectra in the ternary system—the disappearance of the C=O (531.8 eV) peak and the appearance of the C=N peak—directly confirm that OCTS can effectively bind to VMT NSs-NH 2 This also indicates that HPA / OCTS / VMT NSs-NH 2 The composites were successfully synthesized. The XPS analysis results strongly supported the role of OCTS as a cross-linking bridge, promoting an effective cross-linking strategy between amino-functionalized inorganic vermiculite nanosheets (VMT NSs-NH2) and hyperbranched polymers (HPA). Figure 2 As shown, a unique new peak was identified at 1672 cm -1This peak was attributed to the C=N stretching vibration absorption generated by the Schiff base reaction between the aldehyde group of OCTS and the amino group of HPA, indicating that the amino group on HPA can effectively react with the aldehyde group on OCTS, which is consistent with the XPS analysis results and verifies the universality of this chemical reaction pathway. 2 ) revealed a similar new peak at 1675 cm -1 , which is interpreted as the aldehyde group of OCTS and the NH 2 The efficiency of the reaction was confirmed by the unique C=N vibration mode of the Schiff base reaction between amino groups. The Fourier transform infrared spectroscopy (FTIR) results were completely consistent with the reaction mechanism elucidated by the X-ray photoelectron spectroscopy (XPS) data, which strengthened the feasibility of the reaction between OCTS and amino-modified VMT NSs-NH2. It is worth noting that in HPA / OCTS / VMTNSs-NH 2 In the FTIR spectrum analysis of the ternary composite system, 1677 cm -1 The peak at OCTS / HPA and OCTS / VMT NSs-NH 2 This observation strongly suggests that OCTS acts as a cross-linking medium, able to bind to the amino groups of HPA and VMT NSs-NH 2 The amino groups interact with each other, promoting the formation of a hybrid network structure through Schiff base reaction and intermolecular forces.

[0092] Figure 3 The chemical characterization data diagram of the intermediate material and the prepared adhesive in the steps of the present invention.

[0093] like Figure 3As shown in Figure 2, the strength and performance of the adhesive are determined by multiple interactions. First, chemical crosslinking is a key factor in the strength of the adhesive. Sufficient chemical crosslinking is formed through the Schiff base reaction between HPA, OCTS, and VMT-NSs-NH2, which enhances the cohesion of the adhesive. Chemical crosslinking transforms the physical entanglement of linear polymers into a network structure, which significantly improves the cohesion and overall performance of the adhesive. Second, hydrogen bonding plays an important role in the cohesion of the adhesive. The large number of hydrogen bonds formed between HPA, OCTS, and VMT-NSs-NH2 molecules further enhances the cohesion of the adhesive. As a strong physical force, hydrogen bonding is essential for improving the bonding strength of the adhesive. In addition, coordination bonds also play a role in the network structure of the adhesive. The coordination bonds formed between the inorganic components of VMT-NSs-NH2 and HPA and OCTS constitute part of the crosslinked network of the adhesive. The formation of these coordination bonds enhances the cohesion and bonding performance of the adhesive. Finally, the bonding between the adhesive and the adherend cannot be ignored. The large number of hydrogen bonds formed between the adhesive network and the wood board is an important reason for the increase in the bonding strength of the adhesive. These hydrogen bonds make the bond between the adhesive and the adherend stronger, thereby improving the adhesive strength. In summary, the strength and performance of the adhesive are determined by chemical crosslinking, hydrogen bonding, coordination bonds, and the bonding force between the adhesive and the adherend. These interactions together form the crosslinked network of the adhesive, enhancing its cohesion and bonding performance. The consistency of this series of infrared spectroscopy data directly proves the successful preparation of the HPA / OCTS / VMT NSs-NH2 composite material and verifies the rationality and feasibility of using OCTS as a crosslinker at the molecular level to achieve efficient crosslinking between amino-modified inorganic vermiculite nanosheets and hyperbranched polymer HPA.

[0094] The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments, and the above embodiments and descriptions are only for explaining the principles of the present invention. Without departing from the spirit and scope of the present invention, the present invention may have various changes and improvements, and the scope of protection of the present invention is defined by the attached claims, description and their equivalents.

Claims

1. A method for preparing an organic-inorganic hybrid flame retardant adhesive, characterized in that The method comprises the following steps: an organic-inorganic hybrid flame retardant adhesive is composed of oxidized chitosan OCTS, a hyperbranched polymer HPA and vermiculite nanosheets VMTNSs-NH2 with surface modified amino groups, and oxidized chitosan, hyperbranched polymer HPA and surface modified vermiculite nanosheets are added respectively, and the organic-inorganic hybrid flame retardant adhesive is prepared through a Schiff base reaction covalent cross-linking reaction.

2. The method for preparing the organic-inorganic hybrid flame retardant adhesive according to claim 1, characterized in that: (1) Prepare oxidized chitosan OCTS, hyperbranched polymer HPA and vermiculite nanosheets VMT NSs-NH2 respectively; (2) mixing oxidized chitosan OCTS and hyperbranched polymer HPA at a molar ratio of 1:1; (3) adding vermiculite nanosheets VMT NSs-NH2 with a mass fraction of 1-10%; (4) The added components are covalently cross-linked through a Schiff base reaction to prepare an organic-inorganic hybrid flame retardant adhesive.

3. The method for preparing the organic-inorganic hybrid flame retardant adhesive according to claim 2, characterized in that: In step (1), preparation of hyperbranched polymer HPA: 0.4 mol of 3-(2-aminoethylamino)propylmethyldimethoxysilane, 0.2 mol of triethanolamine TEA and 0.1% of p-toluenesulfonic acid (p-TSA) are placed in a 250 ml three-necked flask with a distillation apparatus, heated to 120° C. under a nitrogen atmosphere, and maintained at this temperature until the by-product ethanol is distilled off. The temperature of the system is then maintained at 180° C. until no distillation by-product is produced.

4. The method for preparing the organic-inorganic hybrid flame retardant adhesive according to claim 2, characterized in that: In step (1), the preparation of vermiculite nanosheets VMTNSs-NH2: 5.0 g of VMT powder was placed in 500 ml of 36% saturated sodium chloride solution, concentrated and refluxed at 120°C for 2 hours, and after cooling to room temperature, the sample was filtered and rinsed with deionized water and ethanol to remove excess salt; then, the sodium-exchanged VMT was dispersed in 300 ml of 2M solution, refluxed at 120°C for 2 hours and cooled to room temperature, the sample was filtered and rinsed with deionized water, and the collected sample was subjected to tip ultrasound at low temperature below 10°C for 60 minutes, and then the dispersion containing single-layer or multi-layer VMT nanosheets was further separated, and the sample was centrifuged at 3000 rpm for 30 minutes to remove multi-layer / blocky residues. 1 g of VMT NSs was initially dispersed in 50 ml of toluene. Subsequently, a stable suspension was formed by continuous mechanical stirring for 6 hours to ensure that the VMT NSs were evenly distributed in the solvent. This suspension was then transferred to an ultrasonic cleaning tank, during which 6.2 ml of 3-aminopropyltriethoxysilane APTES was gradually added dropwise to promote the binding of APTES molecules to the clay surface. The ultrasonic process lasted for thirty minutes, and after the ultrasonic process was completed, the dispersion was filtered and rinsed with ethanol several times to completely remove the unreacted APTES; finally, the washed clay sample was dried in a vacuum oven at 120 ° C for 12 hours to ensure the complete removal of all solvents and moisture, and the grafted clay was designated as VMT NSs-NH2.

5. The method for preparing the organic-inorganic hybrid flame retardant adhesive according to claim 2, characterized in that: In step (1), oxidized chitosan OCTS is prepared by dissolving 1.0 g of chitosan in 100 ml of acetic acid solution with a concentration of 1% and mechanically stirring at room temperature for 2 hours. Different amounts of sodium periodic acid are dissolved in deionized water, with a weight ratio of oxidant to chitosan of 1.0, and added to the chitosan solution under magnetic stirring; the mixture is heated to 40°C and stirred in the dark for 3 hours; after cooling to room temperature, an appropriate amount of ethanol is added. The white precipitate is separated by filtration and washed three times with deionized water; finally, OCTS is dried at room temperature for 24 hours.

6. The method for preparing the organic-inorganic hybrid flame retardant adhesive according to claim 1 obtains the organic-inorganic hybrid flame retardant adhesive.

7. A wood bonding method using the organic-inorganic hybrid flame retardant adhesive according to any one of claims 1 to 3, characterized in that The method comprises the following steps: applying the adhesive to the wood surface, hot pressing at 100-180°C for 240-600 seconds, and then placing at room temperature for 24 hours to eliminate internal stress.

8. A method for preparing a flame retardant coating, characterized in that The method comprises the following steps: dissolving disodium octaborate tetrahydrate hydrate in water to form a transparent solution, and then brushing the solution on the surface of the plywood bonded with the flame retardant adhesive.

9. A method for preparing a flame retardant plywood, characterized in that The method comprises the following steps: using the bonding method described in claim 7.